Artillery-Missile System Control Under Disturbances Conditions Using a Modified Computed Torque Control Method - Piotr SZMIDT (Problemy Mechatroniki)
The paper addresses the issue of remote control of a artillery-missile system when the system is affected by dynamic and kinematic disturbances. The dynamic disturbances analysed in the paper includes disturbances from shots fired while kinematic disturbances are excitation related to the motion of the base on which the system is installed. The object of the study is a system model based on the ZU-23-2MR artillery-missile system produced and operated in Poland, designed to combat lightly armoured air, naval and ground targets. Once the system model and the assumed disturbance types are discussed, further in the paper the system control in azimuth and elevation angular position is analysed. Computed torque control with additional corrective components is presented. A certain inertia in system drive models is also adopted. Additionally, uncertainty of model identification is assumed, i.e. object control parameters are different from the parameters of the model which serves as basis for calculating the control parameters. Differences in weights, mass moments of inertia and friction torques arising in the system's drive elements are taken into account. The last part of the paper includes an analysis of the speed of target interception and precision of tracking a manoeuvring aerial target with the interference affecting the system. It was assumed that the system is located on a ship, therefore kinematic disturbances are related to the ship's movement on the sea waves, as well as dynamic disturbances are related to firing the weapon. All simulations were performed in the Scilab environment for a non-linear model of the system. Essential results are shown in a graphical form.